NCMP-02. MULTIPLE SCLEROSIS OUTCOMES AFTER CANCER IMMUNOTHERAPY. (5th November 2018) - Garcia, Catherine; Adams, Val; Anthony, Lowell; Villano, John
Abstract: INTRODUCTION: Multiple sclerosis as an adverse event of immune checkpoint inhibitors (ICI) is rare and the outcomes remain largely unknown with limited descriptions in the literature. METHODS: We analyzed the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database, our institutional records, and the literature for pembrolizumab, atezolizumab, nivolumab, ipilimumab, avelumab, and durvalumab two years prior their FDA approval to December 31, 2017, for all cases of newly diagnosed or MS relapse. RESULTS: We identified 14 cases; 11 cases from FAERS, 1 case was identified from our institution, and 2 cases from the literature. The median age was 52.5 years, with 42.8% males and 42.8% females. Indications for ICI included melanoma (6 patients), non-small cell lung carcinoma (2 cases), pleural mesothelioma (1 case), renal cell carcinoma (1 case), colorectal cancer (1 case), and was not reported in 2 cases. Two cases were identified from pembrolizumab use, 6 cases with nivolumab, 1 case with atezolizumab, and 5 cases after ipilimumab use. No cases were reported with the use of avelumab or durvalumab. History of multiple sclerosis was confirmed in 8 cases. Mean time to beginning of symptoms was 29 days (3 cycles). The median time to beginning of symptoms was longer in patients receiving ipilimumab (45 days, 4 cycles). Median time for symptom resolution in all the patients was 2 months. All cases required hospitalization, further treatment, and close follow up. Two patients died after starting therapy. CONCLUSIONS: MS may be associated with overall state deterioration, significant disability, and death. The benefits of ICI should be carefully assessed prior to beginning therapy in patients with a history of MS.